Supercomputing Frontiers 7th Asian Conference, SCFA 2022, Singapore, March 1-3, 2022, Proceedings - Panda, Dhabaleswar K.; Sullivan, Michael (Lecture Notes in Computer Science, 2022)
This open access book constitutes the refereed proceedings of the 7th Asian Conference Supercomputing Conference, SCFA 2022, which took place in Singapore in March 2022. The 8 full papers presented in this book were carefully reviewed and selected from 21 submissions. They cover a range of topics including file systems, memory hierarchy, HPC cloud platform, container image configuration workflow, large-scale applications, and scheduling.